Molecular cloning and primary nucleotide sequence analysis of a distinct human immunodeficiency virus isolate reveal significant divergence in its genomic sequences. - Desai, S M (1986)
In an effort to evaluate data on genomic relatedness among the various human immunodeficiency viruses (HIVs), we have molecularly cloned a virus isolate designated HIV (CDC-451). Preliminary characterization of the HIV (CDC-451) clone indicated that the restriction enzyme map was distinct from those of other known HIV isolates. Analysis of the primary nucleotide sequence of the regions encoding the structural proteins and comparison with sequences known for other HIV isolates indicated substantial differences for HIV (CDC-451). The sequences encoding the group-specific antigen gene, although they showed some variation, were conserved to a greater extent than were those encoding envelope proteins. In the envelope gene sequences, most of the changes (up to 24.5% divergence) were located in the amino-terminal region encoding a glycoprotein with a Mr of 120,000. The carboxyl-terminal region, encoding a protein of Mr 41,000, was more highly conserved. The variation in the sequences encoding envelope proteins may have important implications for the antigenic properties and/or pathogenicity of the disease and for its detection and ultimate eradication.